Natural deep eutectic solvents-based green extraction of vanillin: optimization, purification, and bioactivity assessment - Xu, Lingxia; Liaqat, Fakhra; Khazi, Mahammed Ilyas; Sun, Jianzhong; Zhu, Daochen (Frontiers in Nutrition, 2024)
The sustainable extraction of natural compounds has recently attracted significant attention. The extraction of high-quality natural vanillin in active form is crucial for its efficient use in various industries, but conventional solvents are not suitable for this purpose. The flammability, volatility, and toxicity of organic solvents can harm extraction personnel, and their waste liquid can cause environmental pollution. Natural deep eutectic solvents (NADES) are cost-effective, environmentally friendly, biodegradable, and non-toxic organic alternative to conventional solvents. In this study, 20 different NADES were tested for the sustainable extraction of natural vanillin. Among these, a DES system composed of choline chloride: 1,4-butanediol: lactic acid exhibited the highest extraction rate (15.9 mg/g). Employing response surface methodology (RSM), optimal extraction conditions were determined, yielding a vanillin content 18.5 mg/g with water content of 33.9%, extraction temperature of 64.6°C, extraction time of 32.3 minutes, and a solid-liquid ratio of 44.9 mg/mL. Subsequently, the optimized NADES system was then assessed for reusability in extracting vanillin from vanilla pods and kraft lignin over three cycles, retaining 43% of its extraction efficiency and demonstrating potential for waste reduction. Purification of vanillin was achieved through chromatography using a non-polar resin SP700, with ethanol as a desorption eluent and a feed solution pH of 4.0, resulting in the highest vanillin purity. HPLC and GC-MS analyses confirmed purity, while antioxidant activity assays (DPPH and ABTS) showcased significant antioxidant activity of the purified vanillin. Moreover, vanillin exhibited notable antimicrobial activity against a panel of food-borne bacteria. This study introduces an environmentally friendly approach to vanillin extraction highlights using NADES, emphasizing the potential for producing high-quality bioactive vanillin with reduced environmental impact. The applicability of NADES systems extends beyond vanillin, offering a versatile method for extracting diverse natural compounds.